Elementary Reduction of Matrices over Right 2-Euclidean Rings - Romaniv, A. M.; Романів, О. М. (Institute of Mathematics, NAS of Ukraine, 2004)
We introduce a concept of noncommutative (right) 2-Euclidean ring. We prove that a 2-Euclidean ring is a right Hermite ring, a right Bezout ring, and a GE n -ring. It is shown that an arbitrary right unimodular string of length not less than 3 over a right Bezout ring of stable rank possesses an elementary diagonal reduction. We prove that a right Bezout ring of stable rank 1 is a right 2-Euclidean ring.